Lyotropic liquid crystal mesophases as transdermal delivery systems for lipophilic drugs: A comparative study - de Araujo, Guilherme Rodolfo Souza; Azevedo Lima, Odeanny Vitória; Barreto Neujahr, João Pedro; Matos, Saulo Santos; de Souza, Thalisson Amorim; dos Santos, Aline Martins [UNESP]; Chorilli, Marlus [UNESP]; de Souza Araujo, Adriano Antunes; Duarte, Marcelo Cavalcante; da Cunha Gonsalves, Joyce Kelly Marinheiro; de Souza Nunes, Rogéria; dos Santos, Marcio Roberto Viana; et al. (Elsevier, 2023)
The present work aimed to evaluate different Liquid Crystal Mesophases (LCM) as transdermal drug delivery systems (TDDS) for nifedipine (NFD), a lipophilic drug model. The formulations composed of water, Citrus sinensis essential oil (CSEO), PPG-5-CETETH-20, and Olive oil ester PEG-7 were obtained and characterized by polarized light microscopy (PLM), rheology, small-angle x-ray scattering (SAXS), Fourier transform infrared coupled with an attenuated total reflection accessory (FTIR-ATR) and in vitro assays: bioadhesion, drug release, skin permeation, and retention tests. As a result, changes in component proportions led to several transparent viscous systems with an anisotropic profile. PLM and SAXS proved the presence of lamellar (S1), hexagonal (S3), and lamellar + hexagonal (S2) LCM, and rheology showed a high viscoelasticity profile. LCMs were able to adhere to the skin, and S2 achieved higher adhesion strength. NFD (5 mg/mL) has not modified the organization of LCMs. Results also showed that S3 promoted higher permeation and retention and higher disorganization of stratum corneum lipids, which is the main permeation-enhancing mechanism. Thus, the formulations obtained can carry and improve drug delivery through the skin and are promising TDDS for lipophilic drug administration, such as NFD.
Keywords: Lyotropic liquid crystal; Nanostructured system; Pharmaceutical nanotechnology; Transdermal drug delivery system